Indigenous Perceptions of the End of the World Creating a Cosmopolitics of Change - Bold, Rosalyn (Palgrave Studies in Anthropology of Sustainability, 2019)
This edited volume constructs a 'cosmopolitics' of climate change, consulting small-scale sustainable communities on whether the world is ending and why, and how we can take action to prevent it. By comparing scientific and indigenous accounts of the same phenomenon, contributors seek to broaden Western understandings of what climate change constitutes. In this context, existing cosmologies are challenged, opening spaces for hegemonic narratives to enter into conversation with the non-modern and construct 'worlds otherwise'-situations of world change and renewal through climate change. Bold brings together perspectives from Central America, Mexico, the Amazon, and the Andes to converse with scientific narratives of climate change and create cracks that bring new worlds into being for readers. The chapter "Fragile Time: The Redemptive Force of the Urarina Apocalypse" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.